Development and Validation of a “Pelita Harapan” Questionnaire Assessing Knowledge, Attitude, and Practice Toward Coronavirus Disease 2019 Among Young People in Indonesia - Winata, Sharleen; Kurniawan, Andree; Agung, Fransisca Handy; Hardjo Lugito, Nata Pratama; Jodhinata, Claudia; Halim, Devina Adella; Angelina, Stella; Agatha, Cindy Monika (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) has become a pandemic. Much false information was circulating especially through social media and affected individual’s knowledge, attitude, practice (KAP) towards COVID-19. Currently, there is lack of validated questionnaires to assess KAP about COVID-19 especially in Indonesian young people.Aim: To develop and validate a new COVID-19 KAP questionnaire for young people population in Indonesian language.Methods: Some literature review was done to look for the concept to generate a new questionnaire. Open-ended questions were generated to know the baseline knowledge. Then, close-ended questions were formulized for knowledge, attitude, and practice area. The experts and several respondents were asked to give their opinions about the contents of the questionnaire. The validity was examined using Cronbach's alpha coefficient. For reliability, internal consistency was examined by using Pearson or Spearmen correlation test.Results: A total of 59 subjects with median ages 21 (16-24) years old of non-medical individuals were included in this validation process. More than half were male, mostly held bachelor’s degree/diploma, and were dominated with students. This Indonesian COVID-19 KAP questionnaire for young people consists of 10 knowledge, 8 attitude, and 7 practice questions. The Cronbach’s alpha coefficient of knowledge, attitude, and practice areas were 0.87, 0.82, and 0.91, respectively.Conclusions: A questionnaire of KAP towards COVID-19 in Indonesian language had been developed and the results showed good validity.